Strategies for increasing innovation in big pharmaceutical companies - BARBIČ, ŠPELA; KNEZ, LEA; KNEZ, ŠPELA; MLAKAR, TJAŠA; UHAN, SARA; VEZONIK, UROŠ; ČASAR, ZDENKO (Anali PAZU HD, 2023)
The overall technological, scientific and managerial progress of the last few decades is expected to be reflected in increased innovation and research efficiency in many entities, including large pharmaceutical companies. However, often the opposite can be observed. The efficiency of research and development (R&D), which can also be described as the input-output ratio, usually estimated by the number inhouse developed and launched medicines on the market or published scientific publications and granted patents, has been steadily declining in recent decades in the pharmaceutical industry. Nevertheless, especially in recent years many companies have shown successful resistance to this trend with an obvious increase in innovation, which among other things can be attributed to the improved financial efficiency and the design of new R&D models.